PENERAPAN DESIGN THINKING DALAM PENGEMBANGAN ANTARMUKA PENGGUNA WEBSITE KEUANGAN DI CV XYZ - Randy, Rexanne Celesta; Hamdani, Dani (Jurnal Ilmiah Rekayasa dan Manajemen Sistem Informasi, 2024)
CV. XYZ is a fashion industry company focused on selling imported second-hand clothes with various quality levels. To support its business operations, CV. XYZ requires a user interface (UI) for its website that is intuitive, user-friendly, and efficient. Currently, the UI of CV. XYZ's website faces several issues that hinder user experience and operational efficiency. This study aims to explore the application of Design Thinking in developing the financial website UI at CV. XYZ. The research methods include problem analysis and literature review on UI development methods such as Human-Centered Design (HCD) and User-Centered Design (UCD). Design Thinking was chosen as a solution due to its holistic and structured approach that integrates creativity and innovation. The results show that applying Design Thinking can improve the quality of the UI of CV. XYZ's website. The Design Thinking process, which involves a deep understanding of user needs, creative brainstorming, rapid prototyping, and continuous iteration, successfully creates a more intuitive, user-friendly, and efficient UI. This application also enhances user satisfaction and supports the company's operational success. This study provides significant contributions to improving UI quality in the financial industry and offers recommendations for other companies looking to adopt a similar approach.